Wayward Pines. The complete second season [videorecording (DVD)] - Patric, Jason; Kaur, Nimrat; Helman, Josh; Hounsou, Djimon, 1964-; Crouch, Blake (Twentieth Century Fox Home Entertainment, 2018)
"From executive producer M. Night Shyamalan (The Sixth Sense), and based on the rich world created by international best-selling author Blake Crouch, comes the psychological thriller, Wayward Pines. Starring Jason Patric (Rush), Djimon Hounsou (Blood Diamond) and Hope Davis (TV's The Newsroom), Season Two finds the residents of Wayward Pines battling for the survival of the human race against the iron-fisted rule of the First Generation. As the mysteries of the remote town deepen, secrets are unearthed and horrors discovered. Who will survive the civil war in Wayward Pines?"--Jbhifi.com.au.